Pengembangan Assesment Pembelajaran Pendidikan Agama Islam pada Lembaga Pendidikan Islam Dalam Era Digital - Arman Paramansyah; Nurfitriah Nurfitriah; Esa Hari Wibowo; Fajrul Hamdi; Ekawati Ekawati; Fatimah Dzakiroh (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
his study aims to determine the efforts to develop an assessment of Islamic learning educational institutions in the digital era. The method used is a qualitative methodology with an analiys approach. The data obtained is based on the facts in the field and not designed by researches through research. The process of assessing Islamic religious education in this digital era makes it more effective and efficient by paying attention to Islamic teaching. Keywords: assessment, islamic religious education, and digital era